Invasion of Spores of the Arbuscular Mycorrhizal Fungus Gigaspora decipiens by Burkholderia spp. - Levy, Avram (American Society for Microbiology, 2003)
Burkholderia species are bacterial soil inhabitants that are capable of interacting with a variety of eukaryotes, in some cases occupying intracellular habitats. Pathogenic and nonpathogenic Burkholderia spp., including B. vietnamiensis, B. cepacia, and B. pseudomallei, were grown on germinating spores of the arbuscular mycorrhizal fungus Gigaspora decipiens. Spore lysis assays revealed that all Burkholderia spp. tested were able to colonize the interior of G. decipiens spores. Amplification of specific DNA sequences and transmission electron microscopy confirmed the intracellular presence of B. vietnamiensis. Twelve percent of all spores were invaded by B. vietnamiensis, with an average of 1.5 × 10(6) CFU recovered from individual infected spores. Of those spores inoculated with B. pseudomallei, 7% were invaded, with an average of 5.5 × 10(5) CFU recovered from individual infected spores. Scanning electron and fluorescence microscopy provided insights into the morphology of surfaces of spores and hyphae of G. decipiens and the attachment of bacteria. Burkholderia spp. colonized both hyphae and spores, attaching to surfaces in either an end-on or side-on fashion. Adherence of Burkholderia spp. to eukaryotic surfaces also involved the formation of numerous fibrillar structures.